2015
DOI: 10.1111/1556-4029.12910
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Maxillary Dental Arcade Curvature and the Estimation of Biological Ancestry in Forensic Anthropology

Abstract: Previous studies suggest that palate shape is a useful indicator of biological ancestry in human remains. This study evaluates interobserver error in ancestry estimation using palate shape and explores palate shape variation in Gullah (descendants of West Africans) and Seminole (Indigenous American) population samples using geometric morphometric analysis. Ten participants were asked to ascribe biological ancestry and shape to 28 dental casts based on a classification scheme employed in previous studies. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…72,98 Notable limitations on the published studies include a limited age span of early adolescence (12-15 years old), to ascertain minimal tooth wear. Clark et al 105 assessed the maxillary dental arcade curvature for possible inter-population variance but showed low classification accuracy rates.…”
Section: Geometric Morphometrics (Gmm)mentioning
confidence: 99%
“…72,98 Notable limitations on the published studies include a limited age span of early adolescence (12-15 years old), to ascertain minimal tooth wear. Clark et al 105 assessed the maxillary dental arcade curvature for possible inter-population variance but showed low classification accuracy rates.…”
Section: Geometric Morphometrics (Gmm)mentioning
confidence: 99%
“…There also may have been a concern that revealing error rates might appear to lessen the method's relevance or render it inadmissible (e.g., [15]). Some researchers have interpreted Daubert as having an implied minimum level of accuracy for methods to be admissible [16,17], while others have created standards, stating that a method must have an accuracy rate of at least 80% and observer error rates less than 10% in order to be admissible under Daubert [18], or that 90% coverage for an age estimate meets the reliability standard outlined in Daubert [19]. These are over-interpretations of the Daubert guidelines, which do not address acceptable limits for accuracy or error rates (which may vary depending on the discipline, the method, or even the context of a particular case).…”
Section: Introductionmentioning
confidence: 99%
“…Using a curve fitting approach, they found that in the majority of cases the shape of the palate matched an elliptical, hyperbolic, and parabolic profile and that there was a tendency to cluster by palate shape along ancestral lines. Although most of these forensic studies have generally reported the ability to successfully discriminate ancestry on the basis of palate shape, Clark et al, 7 applying a geometric morphometric approach, found little evidence to support palate shape differences between African-derived and Indigenous American groups. Questions remain, therefore, about the degree and consistency with which palate shape differs among some populations.…”
mentioning
confidence: 99%